2019
DOI: 10.3892/ijo.2019.4732
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and functions of Ehm2 transcript variants in lung adenocarcinoma

Abstract: Ehm2 [also known as erythrocyte membrane protein band 4.1-like protein 4B (EPB41L4B)] is a member of the NF2/ERM/4.1 superfamily. The overexpression of Ehm2 has been observed in metastatic cancer cells. Through alternative splicing, the Ehm2 gene produces two transcript variants that encode the two different isoforms, Ehm2/1 and Ehm2/2. The biological functions of these different Ehm2 transcript variants remain unclear. The present study aimed to determine the expression of the Ehm2 variants in lung adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The results of the co-expression analysis performed in the present study identified a significant positive correlation between GIPC2 and EPCAM, LRRC8D, EPB41L4B, ACSL5 and CDS1. Several of these genes have been reported to serve important roles in maintaining normal intestinal mucosal function and cancer resistance (31)(32)(33)(34)(35), thus indicating that GIPC2 and its co-expressed genes may serve as potential prognostic markers for COAD. At present, a large number of studies have shown that members of the GIPC family are able to fully exert their role as adaptors and interact with a variety of proteins, including RGS19/GAIP, MY06 and type III TGF-P receptors, and subsequently participate in the regulation of a variety of biological processes, including cell signaling, transmembrane protein transport, cell movement and endocytosis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the co-expression analysis performed in the present study identified a significant positive correlation between GIPC2 and EPCAM, LRRC8D, EPB41L4B, ACSL5 and CDS1. Several of these genes have been reported to serve important roles in maintaining normal intestinal mucosal function and cancer resistance (31)(32)(33)(34)(35), thus indicating that GIPC2 and its co-expressed genes may serve as potential prognostic markers for COAD. At present, a large number of studies have shown that members of the GIPC family are able to fully exert their role as adaptors and interact with a variety of proteins, including RGS19/GAIP, MY06 and type III TGF-P receptors, and subsequently participate in the regulation of a variety of biological processes, including cell signaling, transmembrane protein transport, cell movement and endocytosis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with Ehm2/2, 382 amino acids are absent from the carboxyl-terminal region of Ehm2/1 (20). The two Ehm2 isoforms have distinct expression patterns in various cancers, including lung adenocarcinoma (LUAD) and breast cancers ( 22 ). Our previous study demonstrated that the two isoforms of Ehm2 played different roles in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that the two isoforms of Ehm2 played different roles in LUAD. Overexpression of Ehm2/1 exerted inhibitory effects, while knockdown of Ehm2/1 promoted the growth, invasion and migration of A549 cells in vitro ( 22 ). In this study, we focused on the role of Ehm2/1 in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, there are some reports exploring the function of these signatures in other cancers. For example, HHLA2 is a new immune checkpoint in ccRCC, (Zhang et al 2020) EPB41L4B (Ehm2) has been proven to promote the proliferation and invasion of lung cancer cells, (Li et al 2019) IFI16 can impact the immune reaction, (Sui et al 2019) XAF1 has a function related to tumor apoptosis, (Jeong et al 2018) and CMTM3 has been reported to be a promoter in gastric cancer. (Yuan et al 2017) Compared with other studies, our study searched for biomarkers in multiple databases (TCGA, CPTAC, and HPA) and at multiple levels (DNAm, mRNA expression, and protein abundance).…”
Section: Discussionmentioning
confidence: 99%